2014
DOI: 10.1073/pnas.1414576112
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 controls follicular helper T-cell differentiation by regulating the strength of CD28 engagement

Abstract: Cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) is an essential regulator of T-cell responses, and its absence precipitates lethal T-cell hyperactivity. However, whether CTLA-4 acts simply to veto the activation of certain clones or plays a more nuanced role in shaping the quality of T-cell responses is not clear. Here we report that T cells in CTLA-4-deficient mice show spontaneous Tfollicular helper (T FH ) differentiation in vivo, and this is accompanied by the appearance of large germinal centers (GCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
155
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(164 citation statements)
references
References 66 publications
9
155
0
Order By: Relevance
“…Despite down-regulation of some eTreg-associated genes, CD25 − Tfr cells maintained their expression of the majority of suppressive molecules, most critically CTLA-4, which we and others have demonstrated to have a key role in Tfr-dependent control of Tfh function (41)(42)(43). Notably many of the genes down-regulated in CD25 − Tfr cells, such as Klrg1, Itgae (CD103), Prdm1 (BLIMP-1), Il10, and Gzmb (Granzyme B), are IL-2-dependent (34).…”
Section: Discussionmentioning
confidence: 71%
“…Despite down-regulation of some eTreg-associated genes, CD25 − Tfr cells maintained their expression of the majority of suppressive molecules, most critically CTLA-4, which we and others have demonstrated to have a key role in Tfr-dependent control of Tfh function (41)(42)(43). Notably many of the genes down-regulated in CD25 − Tfr cells, such as Klrg1, Itgae (CD103), Prdm1 (BLIMP-1), Il10, and Gzmb (Granzyme B), are IL-2-dependent (34).…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, recent studies reported that CTLA-4 controls B cell responses by intrinsic and extrinsic mechanisms (36)(37)(38), in particular at the T follicular helper cell level, a specialized subset of memory lymphocytes (39)(40)(41). Although SRBC challenge is considered as a Tdependent primary humoral response model in rodents, baboons (but also other Old World primates, apes, and humans) are naturally immunized against anti-Gal carbohydrate residues (26) expressed by microorganisms and also other mammals (e.g., sheep).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have implicated persistent antigen presentation in Tfh differentiation [117,143], a notion that might fit with the inability of self-antigens to be cleared in autoimmune settings. Interestingly, Tfh differentiation is subject to regulation by a number of pathways that are linked genetically to autoimmunity, including the CD28/cytotoxic T lymphocyte antigen (CTLA)-4 axis [144][145][146][147][148][149][150], IL-2 [127][128][129][130] and the lymphoid-specific tyrosine phosphatase (LYP) encoded by protein tyrosine phosphatase, non-receptor type 22 (PTPN22) [151]. The link between these loci and disease initiation is complex, but modulation of Tfh differentiation adds an additional consideration to the other known roles of the candidate genes in these locations.…”
Section: Il-2 Signalling Impairs Tfh Differentiationmentioning
confidence: 99%